2020
DOI: 10.1103/physrevb.102.024410
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic cluster-glass phase in Ca(Co1xIrx)2yAs2

Abstract: Single crystals of Ca(Co1−xIrx)2−yAs2 with 0≤x≤0.35 and 0.10≤y≤0.14 have been grown using the selfflux technique and characterized by single-crystal x-ray diffraction (XRD), energy-dispersive x-ray spectroscopy, magnetization M, and magnetic susceptibility χ measurements versus temperature T, magnetic field H, and time t, and heat-capacity Cp(H,T) measurements. The XRD refinements reveal that all the Ir-substituted crystals crystallize in a collapsed-tetragonal structure as does the parent CaCo2−yAs2 compound.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
6
2
Order By: Relevance
“…This result contrasts with the calorimetric properties of Ca(Co 1−x Ir x ) 2−y As 2 crystals where γ significantly increases with increasing Ir concentration [56].…”
Section: Heat-capacity Measurementscontrasting
confidence: 75%
“…This result contrasts with the calorimetric properties of Ca(Co 1−x Ir x ) 2−y As 2 crystals where γ significantly increases with increasing Ir concentration [56].…”
Section: Heat-capacity Measurementscontrasting
confidence: 75%
“…Iron and cobalt pnictide metals harbor weak to moderate magnetism driven by features in their electronic band structure lying close to the Fermi energy E F . Tuning the chemical composition of such materials has resulted in intriguing properties related to the underlying magnetism including non-Fermi liquid behavior [1], magnetic glassiness [2], electronic nematicity [3], as well as unconventional superconductivity [4][5][6]. While often discussed using a local-moment description [7][8][9], it is clear that the itinerant nature of the magnetism in these compounds is essential for facilitating the tunability of these phenomena.…”
mentioning
confidence: 99%
“…In a magnetic system with FM quantum fluctuations a C/T ∼ ln T contribution is observed [27,30,[66][67][68][69][70][71]. We found that the zero-field C p (T ) at low T of the x = 0.11, 0.16, 0.21, 0.31, 0.41, and 0.52 crystals can also be well described by…”
Section: Heat Capacitymentioning
confidence: 88%
“…The fitted parameters are listed in Table V. The FM spin fluctuations are observed over a wide composition range in Ca(Co 1−x Ni x ) 2−y As 2 in contrast to the ranges observed in isostructural Sr(Co 1−x Ni x ) 2 As 2 [27] and Ca(Co 1−x Ir x ) 2−y As 2 [30] crystals where the spin fluctuations were limited to narrow composition ranges. The Sommerfeld coefficient γ in Table V increases by nearly a factor of two with only 3-5% Ni substitutions, indicating a corresponding rapid increase in the electronic density of state at the Fermi energy D(E F ).…”
Section: Heat Capacitymentioning
confidence: 97%
See 1 more Smart Citation